2016
DOI: 10.1248/cpb.c16-00359
|View full text |Cite
|
Sign up to set email alerts
|

A New Resin Glycoside, Muricatin IX, from the Seeds of <i>Ipomoea muricata</i>

Abstract: A new resin glycoside, named muricatin IX (1), was isolated from the seeds of Ipomoea muricata (L.) JACQ. (Convolvulaceae). The structure of 1 was determined on the basis of spectroscopic data as well as chemical evidence. Compound 1 is the first representative of resin glycosides in which an organic acid connects the sugar moiety and the aglycone moiety to form macrocyclic ester ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The structure of 136 was determined on the basis of spectroscopic data as well as chemical evidence. It should be noted that 136 is different from all the resin glycosides isolated so far, in that the carboxyl group of its aglycone moiety is linked with a hydroxyl group of the organic acid, which was attached to a sugar moiety by ester linkage, to form a macrocyclic ester ring [60] (Fig. 11).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of 136 was determined on the basis of spectroscopic data as well as chemical evidence. It should be noted that 136 is different from all the resin glycosides isolated so far, in that the carboxyl group of its aglycone moiety is linked with a hydroxyl group of the organic acid, which was attached to a sugar moiety by ester linkage, to form a macrocyclic ester ring [60] (Fig. 11).…”
Section: Introductionmentioning
confidence: 99%
“…The methanol extract of I. muricata seeds afforded a new resin glycoside muricatin IX (34), which composes of muricatic acid C as glycosidic acid, along with one Nla unit aclyated at C-3 position of the Qui″ unit. 58 The carboxyl group of the aglycone moiety linked with the hydroxyl group of the Nla, making muricatin IX (34) the first representative of resin glycosides in which an organic acid connects the sugar moiety and the aglycone moiety to form macrocyclic ester ring. Moreover, four other resin glycosides derived from muricatic acid C, calonyctins F-H (35)(36)(37) and calonyctin J (38), were also identified from the seeds of I. muricata.…”
Section: Muricatic Acid Cmentioning
confidence: 99%
“…1) Noda et al reported that alkaline hydrolysis of the crude resin glycoside fraction of the seeds of I. muricata yielded three organic acids, namely, isobutyric, 2S-methylbutyric, and 2R-methyl-3R-hydroxybutyric (2R,3R-nilic) acid; and a glycosidic acid fraction composed of L-rhamnose, D-fucose, D-quinovose, and 11R-hydroxyhexadecanoic (jalapinolic) acid, 1) whose absolute configuration was later corrected as S. 2) They also discussed the isolation and structural elucidation of three glycosidic acids, namely, muricatic acids A-C. 1,3) Eight genuine resin glycosides having macrolactone structures (jalapins), 4) namely, muricatins I-VIII were also reported. 3,5) In a previous paper, we reported the isolation and structural elucidation of a new type of resin glycoside, namely, muricatin IX, from the seeds of I. muricata, in which an organic acid connects the sugar moiety and the aglycone moiety to form a macrocyclic ester ring. 6) Recently, Wang et al reported the isolation and structural elucidation of nine jalapins, namely, calonyctins B-J, from the seeds of I. muricata, four of which were structurally similar to muricatin IX.…”
Section: Introductionmentioning
confidence: 99%